The Quality of Legal Translation via Neural Machine Software DeepSeek Case Study: جودة الترجمة القانونية من خلال البرامج الآلية العصبية برنامج ديب سيك أنموذجا - BENBALI , Tayyib (Maalim, 2026)
This research aims to assess the quality of legal translation by evaluating outputs from neural machine translation (NMT) applications, specifically DeepSeek program. In fact, NMT has sparked a genuine revolution across multiple domains. Conversely, legal language is a highly technical language characterized by a distinct and precise terminological framework. This necessitates the translator’s mastery of legal texts and his provisions prior to undertaking translation. Consequently, the study shed the light on the following questions: What quality standards are envisaged for legal text translation using NMT programs? Have these systems succeeded in fulfilling the communicative purpose by aligning their computational frameworks with human cognition? And what are the necessary measures that should be adopted to enhance the quality of neural machine translation?